A couple of doubts:

Q1)\(f(x+2y)=f(x)+2f(y)\) given that \(f(1)=2,f(0)=0\)

Q2)\(f(x-f(y))=f(f(y))+xf(y)+f(x)-1\)

Q1)\(f(x+2y)=f(x)+2f(y)\) given that \(f(1)=2,f(0)=0\)

Q2)\(f(x-f(y))=f(f(y))+xf(y)+f(x)-1\)

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

## Comments

Sort by:

TopNewestQ1. Putting \( y' = 2y \), we get \( f(x+y') = f(x) + f(y') \), which is the Cauchy Functional Equation.

Q2 is IMO 1999/Q6 – Siddhartha Srivastava · 1 year, 8 months ago

Log in to reply

– Siddharth G · 1 year, 8 months ago

Thanks for the second! And I made a typo in the first one, I just edited it. SorryLog in to reply

Putting \( x = 0 \), we get \( f(2y) = 2f(y) \).

Now we have \( f(x+y) = f(x+2\frac{y}{2}) = f(x) + 2f(\frac{y}{2}) = f(x) + f(y) \) , from the above statement. Cauchy's Functional Equation all over again. – Siddhartha Srivastava · 1 year, 8 months ago

Log in to reply